Fanaticism as a Worldview - Chouraqui, Frank (Philosophical journal of conflict and violence, 2019)
This article argues in favour of a formal definition of fanaticism as a certain relationship to one’s beliefs that is informed by the assumption that there is a mutual incompatibility between consistency and moderation. It analyses this assumption as an expression of an implicit commitment to naïve realism. It then proposes a critique of such realism and finally it sketches an ontological alternative, able to philosophically and politically respond to and oppose fanaticism by showing the compossibility, on that ontological view, of moderation and consistency